2001
DOI: 10.1071/ar01014
|View full text |Cite
|
Sign up to set email alerts
|

A long-term experiment to study the role of mulches in the physiology and macro-nutrition of strawberry grown under water stress

Abstract: Strawberry (Fragaria × ananassa Duch) cv. ‘Oso Grande’ was grown in the field from July 1999 to May 2000 in order to investigate the effectiveness of different mulch types on fruit yield, quality (i.e. soluble dry matter, fruit size), leaf nutrient compositions, and normal plant growth parameters in strawberry grown under water stress. Treatments were: (1) bare soil + water stressed (WS), (2) bare soil + unstressed (control), (3) black polyethylene mulch + water stressed (BPM + WS), (4) wheat straw mulch + wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 31 publications
8
17
0
3
Order By: Relevance
“…Our results indicate a marked decrease of the total chlorophyll content and increase in carotenoid synthesis (Fig. Further, our results are in agreement with other crops such as eggplant (Solanum melongena L.) (Kirnak et al, 2001), kiwifruit (Actinidia deliciosa C.F. Similar results were found in olive (Olea europaea L.) when subjected to four ET-based irrigation treatments (Doupis et al, 2013).…”
Section: Pigments Cell Membrane Thermostability and Chlorophyll Stasupporting
confidence: 91%
See 3 more Smart Citations
“…Our results indicate a marked decrease of the total chlorophyll content and increase in carotenoid synthesis (Fig. Further, our results are in agreement with other crops such as eggplant (Solanum melongena L.) (Kirnak et al, 2001), kiwifruit (Actinidia deliciosa C.F. Similar results were found in olive (Olea europaea L.) when subjected to four ET-based irrigation treatments (Doupis et al, 2013).…”
Section: Pigments Cell Membrane Thermostability and Chlorophyll Stasupporting
confidence: 91%
“…According to Smirnoff (1993) and Brito et al (2003), the decline in chlorophyll content with soil moisture deficit could be attributed to chlorophyll degradation or decreased synthesis of chlorophyll, together with changes of thylakoid membrane structure. Further, our results are in agreement with other crops such as eggplant (Solanum melongena L.) (Kirnak et al, 2001), kiwifruit (Actinidia deliciosa C.F. Liang & A.R.…”
Section: Pigments Cell Membrane Thermostability and Chlorophyll Stasupporting
confidence: 90%
See 2 more Smart Citations
“…2b). Previous studies also showed that fruit from strawberry plants that received full irrigation had a higher water content and greater berry fresh weight than fruits from plants grown under reduced irrigation (Blatt, 1984;Kirnak, Kaya, Higgs, & Gercek, 2001;Kirnak et al, 2003;Krüger et al, 1999;Liu et al, 2007;Serrano et al, 1992;Terry, Chope, et al, 2007). Fruits from cv.…”
Section: Effect Of DI On Fruit Physiologymentioning
confidence: 91%